Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd004667.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Midwife-led continuity models versus other models of care for childbearing women

Abstract: Most women should be offered midwife-led continuity models of care and women should be encouraged to ask for this option although caution should be exercised in applying this advice to women with substantial medical or obstetric complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
612
3
30

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 724 publications
(682 citation statements)
references
References 78 publications
37
612
3
30
Order By: Relevance
“…Women with defined antenatal risk factors were still eligible for at least some care at the FMU, and uptake of this amongst "higher risk" women is very high. Our findings reflect other studies and reviews of "non-standard" antenatal care (Symon et al 2009;Allen et al 2012;Sandall et al 2013). While observational studies are low in the hierarchy of research evidence, our findings do appear to be a further indicator that there may be something in the antenatal care model which affects the likelihood of preterm birth.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Women with defined antenatal risk factors were still eligible for at least some care at the FMU, and uptake of this amongst "higher risk" women is very high. Our findings reflect other studies and reviews of "non-standard" antenatal care (Symon et al 2009;Allen et al 2012;Sandall et al 2013). While observational studies are low in the hierarchy of research evidence, our findings do appear to be a further indicator that there may be something in the antenatal care model which affects the likelihood of preterm birth.…”
Section: Discussionsupporting
confidence: 82%
“…While several robust evaluations of midwife-led care have demonstrated significant benefits (Sandall et al 2010(Sandall et al , 2013Sutcliffe et al 2012), these have focussed principally on intrapartum care. Many analyses of MLU outcomes do not allow for an evaluation of antenatal care across all risk levels, even when analysing by "intention-to-treat", because women must be considered low-risk at some stage (even if that risk status is revised).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A RCT of group antenatal care, compared to standard care, for young women (aged women randomised to midwife-led continuity of care, compared to standard care, are 378 less likely to give birth preterm (Sandall, et al, 2013). Our study is the first to report 379 similar findings specific to young women; albeit not randomised.…”
mentioning
confidence: 65%
“…In their meta-analysis, Sandall et al (2013) found a higher rate of maternal satisfaction amongst women who received midwifery-led continuity care. There was also a costsaving effect with midwife-led continuity of care compared to other care models (Sandall et al, 2013;Tracy et al, 2013).Women in New Zealand have expressed satisfaction with the LMC model of care (Ministry of Health, 2011). For midwives, providing continuity of care to women is a satisfying way to work, and in itself contributes to sustainable practice (Collins et al, 2010;Edmondson & Walker, 2014;Sandall et al, 2013).…”
mentioning
confidence: 98%